Konversi Kalender dari Hijriyah ke Masehi - Marwadi, Marwadi (Al-Manahij: Jurnal Kajian Hukum Islam, 2009)
A method to define the first day of Qomariyah or Hijriyah months is by rukyatul hilal. It will be esmore perfect when it uses a contemporary hisab method. The data from contemporary hisab sourc (Ephemis and Nautica almanac) are in Masehi calendar system. To find out data for doing the hisab we have to convert from Hijriyah calendar to Masehi calendar.